Echeveria marianae (Crassulaceae), a new species from Jalisco, México - García-Ruiz, Ignacio; Costea, Mihai (Phytotaxa, 2014)
A new species, Echeveria marianae (Crassulaceae) is described from Sierra del Tigre, Valle de Juárez, State of Jalisco, Mexico. The species belongs to ser. Gibbiflorae due to of its acaulescent or short caulescent rosette habit, paniculiform inflorescence, conical-urceolate corolla, and tricolpate pollen grains. Within ser. Gibbiflorae it shares morphological affinities with E. novogaliciana and E. dactylifera from which it differs in the shape, color and margin of leaves, corolla size and color, stamen length, nectaries morphology, and its geographical distribution.